Should abortion be legalized in Malaysia : legal, social and religious perspectives / Namirah Hanum Mohamed Albaki, Nor Arfah Mohd Alib and Tisya Yunus. - Mohamed Albaki, Namirah Hanum; Mohd Alib, Nor Arfah; Yunus, Tisya (2006)
As far back as when humans first became well acquainted with the act of sexual intercourse, there has also been a development in the area of abortion, be it through medieval methods or now through new age, medically and legally approved techniques of removing an unwanted child which has been conceived for whatever reason. Currently, the status of abortion in Malaysia is illegal as governed by the local Penal Code with the exception that it could be done if it was medically certified by a doctor that an abortion should be carried out as giving birth would not only risk the mother's health but possibly endanger her life as well. However, in other various countries from all over the world, their view on the legality of abortion is different as some countries have started to enact laws legalizing abortion to be conducted in the event of a range of conditions, circumstances and reasons. This research has been carried out to determine whether the status of abortion being illegal in the country be changed to cater to the wants and needs of Malaysian society currently as well as whether a woman should be given full legal rights over her body to have an abortion under any condition. This research looks into the issue of abortion through a religious, social and legal point of view. It is based on the qualitative methodology where in, besides referring to books, articles, journals as well as the internet, interviews have been conducted with several lecturers who are well versed in the issue at hand to get a better insight into the topic.